Analysis of the Influence Factors of the Human Development Index in Padang City, West Sumatra - Suryani, Yosi; Rudy Rinaldy (International Ecsis Association, 2023)
This article aims to analyze the influence of GRDP, Life Expectancy, Average Length of School and Number of Poor Population in the 2018-2022 period on the Human Development Index (HDI) of Padang City, West Sumatra Province. The type of data used comes from the Padang City Central Statistics Agency (BPS), West Sumatra Central Statistics Agency (BPS) and Bank Indonesia (BI). While research supporting data also comes from various national and international journals as well as references related to research topics. Data analysis is the Ordinary Least Square (OLS) method, namely multiple regression analysis. The results of the study show that GRDP, life expectancy and average length of schooling are indicators that have a positive and significant impact on the Human Development Index in Padang City, West Sumatra Province. Meanwhile, the indicator for the Number of Poor Population is an indicator that has a negative and significant effect on the Human Development Index. The indicator that has the most dominant effect is the average length of schooling with a standardized coefficient beta of 1.127.